Application of the CIPP Model in Evaluation of The Inclusive Education Curriculum in Madrasah Aliyah - Agus Agus; Minggusta Juliadharma; Mawardi Djamaluddin (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
This research aims to measure the quality of implementation of the inclusive education curriculum using the CIPP evaluation model (context, Input, Process, and Product) at Madrasah Aliyah Negeri 1 Tidore, Madrasah Aliyah Negeri 2 Tidore, Madrasah Aliyah Negeri Insan Cendekia West Halmahera, and Madrasah Aliyah Negeri 1 Ternate. Precisely the fulfillment of the right of all learners to an equitable education that meets their basic learning needs and understands diversity. This research was conducted at Madrasah Aliyah Negeri spread across the province of North Maluku, with the sampling technique used was Stratified Sampling because the researchers divided (stratified) the population on certain characteristics by having four schools as research locations involving the principal, one teacher and one student in each school. The data collection technique used is the implementation scale of the inclusive education curriculum as the main instrument and also a checklist sheet as a reinforcement for the information obtained. The variables in this research are only focused on the implementation of the inclusive curriculum. The result shows that the four schools studied have met the components of context, input, and process in the implementation of the inclusive education curriculum, while the product components have not been fulfilled optimally. This research is also expected to provide focus of attention on educational institutions in providing optimal educational services to students with special needs.